Peran Orang Tua Dalam Membentuk Keshalihan Anak - Ulfa Futri Hasyimiyyah Qissa ‘Ali (ISLAMICA, 2016)
The word shalih is familiar among Muslims, it is only directed to the child that is "righteous child", whereas the meaning of shalih also applies to parents as the first educator, but the mistakes of the parents is often to suppress the purity of his son without correcting himself whether it is in accordance with what is expected to his son, that is to be "righteous parents".